Enterotoxigenic Staphylococcus aureus in the nose of hospital food handlers, João Pessoa, Brazil - Castro, Maria Marluce de Melo Vasconcelos; Iaria, Sebastião Timo (Revista de Saúde Pública, 1984)
Research into the occurrence of S. aureus in the kitchen staffs of several hospitals was carried out. Samples were collected from the nasal vestibules of seventy eight people from eight hospitals in João Pessoa, Paraíba, Brazil. Tests for phagetyping and capacity for enterotoxin production were performed on the strains isolated. The agar Baird-Parker plaque technique was employed to isolate S. aureus incubated at 37°C for 24-48 hours. The following techniques were used to identify the strains isolated: morphology, glucose fermentation/ oxidation and the production test for the following enzimes: catalase, coagulase, desoribonuclease (DNase) and thermonuclease (TNase). The celophane sac culture method was employed to verify the enterotoxigenic capacity of the S. aureus strains. Of the total number of people examined, thirty three (42.3%) were nasal carriers of S. aureus and enterotoxigenic strains were found in five (6.4%). Strains producing staphylococcal enterotoxin type B were found in two of these last, and in the other three, strains producing enterotoxins types C, AE and ABE, respectively. Fifty nine strains were submitted to phagetyping and fifty four strains (91.5%) were shown to be phage-typeable. There was found to be a predominance of strains lysed by phages of group III, followed by those of the "non classified" group, isolated or in association.